Microabrasion: An Effective Method for Improvement of Esthetics in Dentistry - Biji Balan; Chengappa Madanda Uthaiah; Sreejesh Narayanan; Priyadarshini Mookalamada Monnappa (Case Reports in Dentistry)
Enamel microabrasion can eliminate enamel irregularities and discoloration defects, thus improving the appearance of teeth. This paper presents the latest treatment protocol of enamel microabrasion to remove stains on the enamel surface. It has been verified that teeth submitted to microabrasion acquire a yellowish colour because of the thinness of the remaining enamel, revealing the colour of dentinal tissue to a greater degree. Enamel microabrasion is a technique that can be used to correct discoloured enamel. Enamel microabrasion was developed in the mid-1980s as a method of eliminating enamel discolouration defects and improving the appearance of teeth. Several years after the method was developed, much has been learned about this technique, long-term results of treatment, and microscopic changes to the enamel surface that have distinguishable clinical implications. In addition, certain patients can benefit from enamel microabrasion to yield attractive cosmetic results. The aim of this study was to report the clinical case of a male patient of 25 years with moderate fluorosis, whose smile was re-established by the use of an enamel microabrasion technique, with 18% hydrochloric acid and pumice slurry shown to be a safe and efficient method for removing fluorosis stains.